2009
DOI: 10.1002/btpr.113
|View full text |Cite
|
Sign up to set email alerts
|

Mouse × pig chimeric antibodies expressed in Baculovirus retain the same properties of their parent antibodies

Abstract: The development of hybridoma and recombinant DNA technologies has made it possible to use antibodies against cancer, autoimmune disorders, and infectious diseases in humans. These advances in therapy, as well as immunoprophylaxis, could also make it possible to use these technologies in agricultural species of economic importance such as pigs. Porcine reproductive and respiratory syndrome virus (PRRSV) is an arterivirus causing very important economic losses to the industry. Passive transfer of antibodies obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Heterologous expression of mouse–pig chimeric antibody has been reported in Escherichia coli as well as in baculovirus (Jar et al ., ; Pyo et al ., ). Escherichia coli expression system is simple and low costs; however, the expressed proteins may lack important post‐translational modifications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heterologous expression of mouse–pig chimeric antibody has been reported in Escherichia coli as well as in baculovirus (Jar et al ., ; Pyo et al ., ). Escherichia coli expression system is simple and low costs; however, the expressed proteins may lack important post‐translational modifications.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there was no data to show the therapeutic effect of mouse–pig chimeric antibody in animals, although the mouse–pig chimeric antibody have been reported (Jar et al ., ; Pyo et al ., ). In this study, our findings showed that mouse–pig chimeric antibody partially protected mice against lethal challenge with H. parasuis HLJ‐018, suggesting that variable region of chimeric antibody has biologic activity in vivo (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors demonstrated that viral replication was inhibited in a stable Marc-145 cell line expressing Nb6, proving the potential of sdAb (Nb6) as a new form of protection against PRRSV ( 32 ). Similarly, a chimeric mouse x pig antibody anti-linear GP5 epitope had neutralizing activity similar to that of the native mAb (ISU25C1) ( 33 ).…”
Section: Recombinant Antibodies In Immunoprophylaxismentioning
confidence: 99%
“…Several immunoglobulin isotypes from many different species, including murine IgG, 2,3,[21][22][23][24][25] chimeric IgG, [26][27][28][29][30] human IgG, [31][32][33][34][35][36][37][38][39] IgA, [40][41][42] IgM 41 and IgE, [43][44][45] as well as pig Igs 30,45 have been successfully expressed in insect cells. These molecules are all correctly processed (signal peptide cleaved), glycosylated and assembled (H2L2) with a production rate varying from 0.75 to 100 mg/l, depending on the antibody ( …”
Section: Introductionmentioning
confidence: 99%